2016
DOI: 10.1063/1.4939685
|View full text |Cite
|
Sign up to set email alerts
|

Effects of γ-ray radiation on two-dimensional molybdenum disulfide (MoS2) nanomechanical resonators

Abstract: We report on experimental investigation and analysis of γ-ray radiation effects on two-dimensional molybdenum disulfide (MoS2) drumhead nanomechanical resonators vibrating at megahertz frequencies. Given calibrated dosages of γ-ray radiation of ∼5000 photons with energy at 662 keV, upon exposure over 24 or 12 h, all the MoS2 resonators exhibit ∼0.5–2.1% resonance frequency upshifts due to the ionizing γ-ray induced charges and their interactions. The devices show γ-ray photon responsivity of ∼30–82 Hz/photon, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…4), semiconducting MoS 2 (Refs. 3,5-7), and black phosphorus 8,9 , which opens a wide spectrum of emerging applications, such as sensing 10,11 and signal processing with ultralow power and broad tunability 12,13 . Although atomic layer crystals with bandgaps ranging from 0 to 2 eV have been studied in earlier explorations (such as 0 eV graphene 1,2,12 , 0.3-1.5 eV black phosphorus 8,9 , 1.2-1.9 eV MoS 2 (Refs.…”
Section: Introductionmentioning
confidence: 99%
“…4), semiconducting MoS 2 (Refs. 3,5-7), and black phosphorus 8,9 , which opens a wide spectrum of emerging applications, such as sensing 10,11 and signal processing with ultralow power and broad tunability 12,13 . Although atomic layer crystals with bandgaps ranging from 0 to 2 eV have been studied in earlier explorations (such as 0 eV graphene 1,2,12 , 0.3-1.5 eV black phosphorus 8,9 , 1.2-1.9 eV MoS 2 (Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ultralow areal mass density of 3.3 fg/μm 2 , high elastic modulus (~0.3 TPa), and an exceptional strain limit of 10%~12% [14] make it an attractive alternative to graphene, which typically has higher energy dissipation [15], especially in air damping due to a smaller thickness per unit layer and lower mass density [7]. For these reasons, much effort has been made to characterize the resonance behaviors of NEMS devices made of single-layer, few-layer, or multilayer MoS 2 films in a vacuum chamber using electrical or optical excitation at room temperature [16,17,18,19]. Lee et al reported on the demonstration of MoS 2 nanodevices, where MoS 2 diaphragms as thin as 6 nm exhibited fundamental-mode nanomechanical resonances up to ~60 MHz in the very high frequency band, and frequency- Q factor products up to ~2 × 10 10 Hz [16].…”
Section: Introductionmentioning
confidence: 99%
“…Then, Kramer et al experimentally studied the effect of mechanical strain on the dynamics of thin 15-nm-thick MoS 2 nanodrum resonators with a diameter of 5 μm by using a piezoelectric bender to introduce strain [18]. Recently, Lee et al further investigated γ-ray radiation effects on MoS 2 nanodrum resonators with diameters of 5–6 μm by using optical interferometric resonance readout, which vibrates at megahertz frequencies [19]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations